2008
DOI: 10.1108/00251740810911984
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the reasons for the collapse of contemporary companies and their link with the concept of quality

Abstract: PurposeThe purpose of this paper is to explore the link between causes of corporate collapse/demise and the concept of quality.Design/methodology/researchThe paper is informed by a review of literature on corporate collapse and quality management. A literature review and global web search of corporate demises is then conducted. Actual causes of corporate demise are established and compared/contrasted with those in the literature to ascertain any similarities/dissimilarities. The link between causes of corporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…Thus, one single negative service encounter, or service failure, may permanently lower consumers' overall satisfaction and, in turn, may prevent the formation of customer loyalty. A decrease in customer confidence as a consequence of exceptional service failure (depending on the number of customers negatively influenced and/or the degree of impact of the failure) can occur in any organisation, and because of the enormous effects on stakeholders and business viability (Marwa and Zairi 2008;Neir et al 2010) it is an important area for management and academic concern (Pearson and Clair 1998;LaPlant 1999;Bradley and Sparks 2009).…”
Section: Service Failuresmentioning
confidence: 98%
“…Thus, one single negative service encounter, or service failure, may permanently lower consumers' overall satisfaction and, in turn, may prevent the formation of customer loyalty. A decrease in customer confidence as a consequence of exceptional service failure (depending on the number of customers negatively influenced and/or the degree of impact of the failure) can occur in any organisation, and because of the enormous effects on stakeholders and business viability (Marwa and Zairi 2008;Neir et al 2010) it is an important area for management and academic concern (Pearson and Clair 1998;LaPlant 1999;Bradley and Sparks 2009).…”
Section: Service Failuresmentioning
confidence: 98%
“…Specifically, this intimacy with customers can help an organization to obtain information on the improvement and innovation of its products or services, thus enhancing its brand awareness through continuously providing satisfactory customer experiences. According to Marwa and Zairi [79], continuous and excellent quality management is very essential for a company's longevity, which requires the commitment of its every members in their daily work, as well as its active attempt to improve facilities, practices, and methods to deliver better products or services to end customers. In a study of Chinese companies in the service industry, Zhang and Jin [80] find that customer-related CSR is conducive to promoting their success and growth.…”
Section: Business-related Csr and Organizational Resiliencementioning
confidence: 99%
“…Iacovou and Dexter (2005) gave the example of an order entry system project that failed resulting in lost sales of $50 million. Marwa and Zairi (2008) conducted a literature review and found several studies that specified innovation failure as the reason for the demise of firms. In more general terms, it appears that "project cancellations are very costly, with damages exceeding millions of dollars" (Iacovou and Dexter, 2005, p. 184).…”
Section: Hypothesis 3a: Innovation Project Delay Is Negatively Relatementioning
confidence: 99%